Pharmacokinetics of Oral Prednisone at Various Doses in Dogs: Preliminary Findings Using a Naïve Pooled-Data Approach - Sebbag, Lionel; Mochel, Jonathan P. (Frontiers in Veterinary Science, 2020)
This pilot study aimed to determine the plasma pharmacokinetics of prednisone and its active metabolite prednisolone following oral prednisone administration in dogs—using dosing regimens that cover anti-inflammatory to immuno-suppressive biological effects. Six healthy Beagle dogs were given 0.5, 1, 2, and 4 mg/kg prednisone orally once daily for 5 days, each successive course separated by a washout period of 9 days. At steady-state (Day 4), a sparse sampling design allowed for collection of blood from 2/6 individuals for each of the following time points: 0, 15, 30, 60, 90, 120, 240, 480, and 720 min. Prednisone and prednisolone were quantified by liquid chromatography-tandem mass spectrometry (LC-MS/MS). Oral prednisone was rapidly converted to prednisolone in dogs (≤ 30 min), with plasma prednisolone reaching 6-fold greater levels (0–656.1 ng/mL) than prednisone (0–98.8 ng/mL) overall. The ratio of plasma prednisolone/prednisone was constant across the dosing regimens, indicating a non-saturation of the hepatic 11-β-hydroxysteroid dehydrogenase that converts the prodrug to the active metabolite in dogs. The level of both corticosteroids increased with increasing dosing regimens, albeit in a non-linear manner. Non-compartmental pharmacokinetic parameters are described, including peak concentration (Cmax), time of peak concentration (Tmax), area under the concentration-time curve (AUClast), and the elimination half-life (t 1/2) for both corticosteroids, as well as clearance and volume of distribution during the terminal phase (Vz) for the administered drug (prednisone). In sum, the present study utilizes a sparse sampling and naïve pooled-data approach to estimate pharmacokinetic parameters for prednisone and prednisolone, providing supporting preliminary knowledge that can be used to optimize corticosteroid efficacy and minimize toxicity in canine patients.